2011
DOI: 10.1111/j.1525-1446.2011.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

The Decision to Receive Influenza Vaccination Among Nurses in North and South Dakota

Abstract: Educational and social marketing strategies may improve nurse's knowledge about influenza disease and vaccine and increase vaccine uptake. Employers should be encouraged to promote and improve influenza vaccine accessibility in the workplace. Additional study is needed to understand how best to strengthen the influence of intention and habit on the decision of nurses to receive influenza vaccinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…, Johansen et al . ), and one (10%) study was reported each from Switzerland (Falomir‐Pichastor et al . ), Canada (Norton et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, Johansen et al . ), and one (10%) study was reported each from Switzerland (Falomir‐Pichastor et al . ), Canada (Norton et al .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Johansen et al . () reported that 48% of their respondents indicated that the influenza vaccine would give the recipient influenza, with 3% of respondents strongly agreeing that the vaccine can cause the illness. Similarly, Seale et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Other similar factors associated with higher uptake include the belief that influenza prevention is important, 59,73 suffering from a chronic condition 60,62 or having a high-risk person in one's household. 60,62 In addition, the strong effect of habit has been found to be somewhat independent of intent, 74 indicating that convincing HCWs might not be enough. In a pilot Dutch study over 1 season, 73 26.1% of HCWs who intended to get vaccinated eventually did not (they represented 5.2% of the total).…”
Section: Benefits and Risks In Healthcare Settingsmentioning
confidence: 99%
“…PHNs are involved with varying levels of leadership in campaigns to promote immunization (Johansen, Stenvig, & Wey, 2012), private well water testing (Severtson & Henriques, 2009), and community health promotion (Kulbok, et al, 2012). Future research, particularly using an oversized postcard as a second-touch effort is recommended to answer this question.…”
Section: Discussionmentioning
confidence: 99%